RANCANG BANGUN SISTEM PEMESANAN MAKANAN DAN MINUMAN DI RESTORAN ZHAFHA’S HOME BERBASIS WEBSITE - Ike Agusti Hardinata; Wulan Andang Purnomo; Fauzi Tri Yuniko (Jurnal Teknologi Informasi dan Komputer, 2026)
The manual food ordering process at Zhafha's Home Restaurant often results in long lines and long wait times, disrupting customer convenience, especially for office workers with limited rest time. To address this issue, a website-based food ordering system was developed. This system allows customers to order directly through their devices by scanning a QR code provided at the table. Key features include menu display, special promotion information, and digital order data storage. Despite potential challenges such as lack of internet access, the restaurant provides free Wi-Fi and continues to accept manual orders. Implementing this system is expected to improve operational efficiency, service quality, and customer satisfaction, as well as attract new customers.